Analisis Disain Sistem Pengelolaan Dana Desa Menggunakan Model Proses SCRUM - Ginting, Andre Chenaro (Jurnal Algoritma, 2024)
Nagori Purba Dolok village office, Purba District, Simalungun Regency in resolving problems related to village fund management takes a relatively long time. Based on the results of the author's interview with village officials, Mr. Renhard Purba, this is because they still use a simple system, namely using Microsoft Office and village fund data in the office is still stored in an archive. To overcome this problem, additional staff can be done, but this is not appropriate because it will increase the agency's operational costs. So the author designed a village fund management system using HTML5 and PHP technology, which is expected to make it easier to resolve the problems faced by the Nagori Purba Dolok village office. With this system, officers can process village funds easily and provide input to leaders for developing a village fund management system in the future.